Human rabies exposure and associated risk factors in north-west Ethiopia - Azalu, W.W.; Mekonnen, S.A.; Kenubih, A.; Kassa, A.M.; Molla, W.A.; Jemberu, Wudu T. (Elsevier, 2025)
Objectives: The study was conducted to assess community awareness of rabies, and incidence of human rabies exposure and its associated risk factors.